Penerapan Game Kuis Family 100 untuk Meningkatkan Keaktifan Belajar Pendidikan Agama Islam Siswa Kelas XI - Ilham Tri Wahyudhi; Sisfiana Ajeng Anggraeni; Indah Suciani; Hibrul Umam (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Student learning activeness is an important component in achieving effective learning outcomes. However, many classroom learning processes still tend to be teacher-centered, resulting in low student participation. This study aims to analyze the implementation of the Family 100 Quiz Game in improving students' learning activeness in Islamic Religious Education (PAI) learning among eleventh-grade students at SMAN 1 Tambakboyo. This research used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The research was conducted in two cycles involving 38 students. Data were collected through observation sheets, field notes, and documentation. Data analysis was carried out using descriptive quantitative and qualitative techniques by calculating the percentage of student learning activeness. The results showed that the implementation of the Family 100 Quiz Game was able to increase student learning activeness. The average percentage of learning activeness increased from 65% in cycle I to 86% in cycle II. The findings indicate that game-based learning strategies can create a more interactive, collaborative, and enjoyable learning environment. Therefore, the Family 100 Quiz Game can be used as an innovative learning strategy to improve student participation in Islamic Religious Education learning.